Edukasi ‘Tanpa Rokok itu Keren’ untuk Siswa SMP Muhammadiyah Adiwerna Kabupaten Tegal: Penelitian - Nisa, Ikrima Khaerun; Hidayati, Nur Rahmah; Wuryandari, Tutik; Al Fariz, Ibnu As'ad (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Smoking behavior during adolescence constitutes a serious public health concern in Indonesia, given its detrimental effects on physical, psychological, and social well-being. School-based health education represents a crucial preventive strategy for reducing adolescent smoking prevalence. This community service initiative aimed to deliver smoking hazard education to students at SMP Muhammadiyah Adiwerna in Tegal Regency to enhance their knowledge, attitudes, and awareness toward healthy lifestyle practices. The intervention employed multiple approaches, including interactive health promotion sessions, educational video presentations, and pre-test/post-test assessments to evaluate improvements in student comprehension. The activity was implemented using a participatory approach, engaging 127 students from grades VII and VIII. Findings revealed a significant improvement in students' knowledge regarding smoking hazards, demonstrated by an increase in mean scores from 62 in the pre-test to 87 in the post-test. Furthermore, students exhibited considerable enthusiasm throughout the program and successfully identified the adverse effects of smoking on individual health and environmental well-being. This intervention is anticipated to empower students as change agents within their school and family contexts, enabling them to resist smoking solicitations and disseminate smoking-related health information to their peer groups. Moreover, this educational initiative is expected to serve as a foundational step toward achieving a healthy school environment and cultivating a smoke-free youth generation.